Tahap Efikasi Kendiri Guru Dalam Melaksanakan Pengajaran Kekeluargaan (Sains Humanika, 2014)
Family teaching is a sub-topic in five subjects taught at secondary school level namely Home Economics, Moral Education, Physical Education and Health, Civic Education and Citizenship as well as Islamic Education. The main focus of this study was to identify the efficacy level of family teaching especially among teachers of various specialisations. 419 teachers in 50 secondary schools in Peninsular Malaysia were selected as research respondents. The instrument used in the data collection was â€œTeacher Sense of Efficacy Scaleâ€ (TSES) designed by Tschannen Moran and Woolfolk Hoy (2001). The three aspects of teacher self-efficacy studied were teaching strategy, classroom management strategy and student involvement strategy. Findings from the study indicated that the mean value at a range between 6.14 to 6.59 for family teaching efficacy and the three sub-scales. The analysis range between quartiles showed overall family teaching of teachers was moderate. Teacher self-efficacy in the aspects of teaching strategy, classroom management strategy and student involvement strategy were also moderate. Discussion and recommendations for improving family teaching efficacy were presented.
Keywords: Teacher self-eficicacy; family teaching